EFFECTIVENESS OF APPLYING COOPERATIVE LEARNING MODEL OF COMBINATION TYPE THINK PAIR SHARE (TPS) AND TWO STAY-TWO STRAY (TSTS) WITH CONTEXTUAL APPROACH IN MATHEMATICS LEARNING IN GRADE AT SMPN 3 LANGGUDU IN BIMA DISTRICT - Subhanudin, Subhanudin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
The study aims at examining the effectiveness of cooperative learning model combined with Think Pair Share (TSTS) type and Two Stay-Two Stray (TSTS) type with contextual approach in Mathematics learning in grade VIII at SMPN 3 Langgudu in Bima district based on Mathematics learning outcomes, students’ activities, and students’ response. The type of the study was pre-experimental design with one group pretest-posttest design. The populations of the study were all public junior high schools in Langgudu subdistrict of Bima district of academic year 2017/2018 with the total of 17 schools consisted of 497 students of grade VIII. Simple random sampling technique was used to choose the sample regardless the existing strata in population and obtained one school as the experiment, namely SMPN 3 Langgudu with 40 students of grade VIII. The instruments used in this research were observation sheet of learning implementation, learning result test, observation sheet of students’ activities in learning, and questionnaire of students’ response on learning. Data collections consisted of students’ learning result, data of students’ activities in learning, and data of students’ response in learning. Data were analyzed by employing descriptive and inferential analys. The results of the study based on descriptive analys reveal that (1) Mathematics learning outcomes in experiment class is in moderate category with the mean score 75.48, and standard of deviaton 8.25 from the ideal score 100, (2) the classical completeness level in posttest is 85% in complete category, (3) the mean of normalization gain is in moderate category with the mean score 0.60, standard of devation 0.11 from the ideal score 1, (4) the students’ activities in learning is in good category with the mean score 3.3, (5) the students’ response on the implementation of cooperative learning combined with TPS and type TSTS type with contextual approach is in positive category with the mean score 3.3, standard of deviation 0.27 from the ideal score 1. The result based on inferential analysis to examine hypothesis at the level of significance α = 0.05 using one sample t test with SPSS 20 reveals that the data of learning outcomes in posttest, normalized gain, and data of students’ response, it can be concluded that the application of cooperative learning model of Think Pair Share type and Two Stay-Two Stray type with contextual approach is effective to be applied on cube and block learning material in grade VIII at SMPN 3 Langgudu in Bima district.